The Immediate Effects of Muscle Energy Technique on Range of Motion and Isokinetic Muscle Strength in Volleyball Players with Glenohumeral Internal Rotation Deficit: A Randomized Controlled Trial - AYBERK, BAHAR; AVCI, ENDER ERSİN; SARI, ZÜBEYİR (AVES, 2021)
Objective: The purpose of the present study was to investigate acute effects of muscle energy technique (MET) for the posterior shoulder on glenohumeral joint (GHJ) range of motion (ROM) and isokinetic peak torque values of GHJ rotators. Methods: Eighteen male volleyball players volunteered to participate. All participants attended both MET trial for the GHJ horizontal abductors and sham trial. Preintervention and postintervention internal rotation (IR) and external rotation ROM and GHJ rotators isokinetic peak torque values were measured. Repeated measures one-way ANOVA and Bonferroni correction were used for analyzing the differences in the ROM and isokinetic parameters among the trials. Significance was defined as P <= .05. Results: The experimental group had a significantly greater increase in GHJ IR ROM postintervention compared to the control group (P = .005). No significant difference between the experimental group and control group was found for external rotation ROM (P > .05). However, a significant increase between the control/experimental and sham trials was found for external rotation ROM postintervention (P = .005). Besides, 60 degrees internal rotator (P = .001) and external rotator (P = .008), and 180 degrees internal rotator (P = .019) and external rotator (P = .049) peak torque values showed significant increase between the experimental and control/sham trials. Conclusion: A single application of an MET for the posterior shoulder provides immediate improvement in GHJ IR ROM and isokinetic peak torque values of both GHJ internal and external rotators in asymptomatic volleyball players.
Keywords: Volleyball; muscle strength; shoulder joint; POSTERIOR SHOULDER TIGHTNESS; BASEBALL PLAYERS; ADAPTATIONS; PAIN